Market Reaction to BI Rate Policy by Bank Indonesia in 2024 Using GLM-Repeated Measures: A Study of Property and Real Estate Companies on the Indonesia Stock Exchange - Azizah, Elsia Nur; Hasnawati, Sri; Kusumah, Fajrin Satria Dwi (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study focuses on examining the market reaction to the BI Rate increase on April 24, 2024 and the BI Rate decrease on September 18, 2024 in property and real estate sector companies listed on the Indonesia Stock Exchange. This study aims to analyze the market reaction to the BI Rate policy event by Bank Indonesia in 2024. This research uses a type of quantitative research using an event study approach. The method used is the General Linear Model (GLM) with Repeated Measures to test differences in Abnormal Returns and trading volume activity before and after the BI Rate policy announcement. Based on the sample taken, namely Property and Real Estate sector companies, 74 research samples were obtained using a window period of 7 days before and 7 days after the event. The results showed that there was no significant difference in Abnormal Returns and trading volume activity before and after the BI Rate increase and decrease. The findings indicate that there is no capital market reaction or in other words the BI Rate policy event by Bank Indonesia in 2024 has no information content that can be absorbed by investors.